A qualitative examination of coping strategies in international tennis umpires - Murakami, K.; Sakata, S.; Matsuura, M. (Science and Racket Sports VI, 2019)
The role of officials in all sports fields has always been accompanied by stress and anxiety. Tennis judgement is also a very exciting occupation and a stressful one in any stageDAs the best performance cannot be expected from athletes and coaches who are under a great deal of stress, officials are sometimes unable to demonstrate proper performance. Therefore, the purpose of the study was to investigate the coping strategies in the international tennis umpires. Five umpires with International Tennis Association budges of gold, silver, or bronze were interviewed about the coping they experienced as international umpires. At the time of the interview, the average age of the participating umpires was 46.1 yr. with a range of 37 to 52 yr. Qualitative interviews were between 35 and 60 minutes long and were transcribed, coded, and analysed by three experienced qualitative researchers. Forty-one raw data themes were identified from the analysis of the interview data. These raw data responses were content analysed. Dimensions of coping strategies were identified, including problem-solving, positive reappraisal, avoidance, seeking social support, information seeking, and distraction. The information gathered from this work also provides insight into the creation of better stress management programs for this population.